AB0761 SECUKINUMAB FOR THE TREATMENT OF PSORIATIC ARTHRITIS IN REAL LIFE: AN ITALIAN EXPERIENCE. (June 2019) - Martinis, Federica; Caimmi, Cristian; Foti, Rosario; Visalli, Elisa; Amato, Giorgio; Ramonda, Roberta; Ortolan, Augusta; Lorenzin, Mariagrazia; Semeraro, Angelo; Santo, Leonardo; Praino, Emanuela; Chimenti, Maria Sole; et al.
Abstract : Background: Secukinumab is a novel treatment for psoriatic arthritis (PsA) but data from real life are still missing. Objectives: The aim of this study is to evaluate a wide cohort of PsA patients on secukinumab followed in 7 Italian rheumatologic centers. Methods: Two-hundred and seventy-nine patients affected by PsA and on secukinumab were enrolled. Data on disease characteristics, previous and ongoing treatments, comorbidities and duration of follow-up were collected. In particular DAPSA and aSDAS were used to assess articular and axial disease activity. Results: Mean age of our cohort was 53±11 years and BMI 26.4±5.1 kg\m 2 with the majority of patients being female (63.8%). Mean disease duration was 9.7±7.5 years and mean follow-up was 10.9±6.8 years. For 100 patients (35.8%) secukinumab was their first line biologic treatment and 41 (50.5%) were in monotherapy. DAPSA was 25.9±10.5 at baseline, 15.9±9.7 at M3, 12.9±8.4 at M6, 9.8±7.1 at M12 with a significant downward decrease at every visit as compared to baseline (p<0.001 for each comparison to baseline). ASDAS at baseline was 3.27±1.15, 2.32±0.99 at M3, 2.04±1.12 at M6, 1.96±0.88 at M12 with a significant downward decrease at M3 and M6 (p<0.001) and a downward trend for M12 (p=0.064), probably because of the small number of patients with axial involvement at M12 (15). After 12 months of treatment 70.6% with axial involvement and 76.6% with articular manifestations had an inactive disease\low disease activity, accordingly to aSDAS and DAPSA respectively. Forty patients (14.3%) stopped the treatment during the follow up mainly because of primary or secondary loss of efficacy (18 and 10, respectively). Only 9 patients suspended the treatment because of adverse events, of which 5 because of reactions at site of injection. The retention rate at 12 months was very good in the whole population (figure), and in particular in patients with entesitis at the baseline (10.5 vs, 11.2, p=0.038). No differences in survival were found when dividing patients accordingly to BMI, although overweight or obese patients showed a trend for a better retention rate (10.6 vs 10.9, p=0.089). Interestingly no differences were found between naïve and non-naïve patients (p=0.895) and between those in monotherapy or in combination therapy (p=0.925). Conclusion: This is one of the first real life studies on secukinumab and shows a very good efficacy and safety of this treatment in PsA patients, also for the articular manifestations, as shown by a significant decrease of DAPSA over a 12-months follow up. Disclosure of interests: Federica Martinis: None declared, Cristian Caimmi: None declared, Rosario Foti: None declared, Elisa Visalli: None declared, Giorgio amato: None declared, Roberta Ramonda: None declared, augusta Ortolan: None declared, Mariagrazia Lorenzin: None declared, angelo Semeraro: None declared, Leonardo Santo: None declared, Emanuela Praino: None declared, Maria Sole Chimenti: None declared, Roberto Perricone: None declared, Favia Sunzini: None declared, Raffaele Scarpa: None declared, Francesco Caso: None declared, Luisa Costa: None declared, Elena Fracassi Speakers bureau: Novartis, Maurizio Rossini: None declared, antonio Carletto Speakers bureau: Roche, Novartis, MSD, abbvie, Bristol, Jannsen, Celgene, Pfizer